Urine biomarkers of acute kidney injury in noncritically ill, hospitalized children treated with chemotherapy. Issue 10 (18th April 2017) - Sterling, Maya; Al‐Ismaili, Zubaida; McMahon, Kelly R.; Piccioni, Melissa; Pizzi, Michael; Mottes, Theresa; Lands, Larry C.; Abish, Sharon; Fleming, Adam J.; Bennett, Michael R.; Palijan, Ana; Devarajan, Prasad; et al.
Abstract: Background: Cisplatin (Cis), carboplatin (Carb), and ifosfamide (Ifos) are common nephrotoxic chemotherapies. Biomarkers of tubular injury may allow for early acute kidney injury (AKI) diagnosis. Procedure: We performed a two‐center (Canada, United States) pilot study to prospectively measure serum creatinine (SCr), urine neutrophil gelatinase‐associated lipocalin (NGAL), and interleukin‐18 (IL‐18) in children receiving Cis/Carb (27 episodes), Ifos (30 episodes), and in 15 hospitalized, nonchemotherapy patients. We defined AKI using the Kidney Disease Improving Global Outcomes (KDIGO) definition. We compared postchemotherapy infusion NGAL and IL‐18 concentrations (immediate postdose to 3 days later) to pre‐infusion concentrations. We calculated area under the receiver operating characteristic curve (AUC) for postinfusion biomarkers to discriminate for AKI. Results: Prechemotherapy infusion NGAL and IL‐18 concentrations were not higher than nonchemotherapy control concentrations. Increasing chemotherapy dose was associated with increasing postinfusion (0–4 hr after infusion) NGAL ( P < 0.05). Post‐Ifos, immediate postdose, and daily postdose NGAL and IL‐18 were significantly higher than pre‐infusion biomarker concentrations ( P < 0.05), during AKI episodes. NGAL and IL‐18 did not rise significantly after Cis–Carb infusion, relative to predose concentrations ( P > 0.05). NGAL and IL‐18 measured immediately after Ifos infusion discriminated for AKI with AUCs is 0.80 (standard error = 0.13) and 0.73 (standard error = 0.16), respectively. NGAL and IL‐18 were not diagnostic of Cis–Carb‐associated AKI. When AUCs were adjusted for age, all biomarker AUCs (Cis–Carb and Ifos) improved. Conclusion: Urine NGAL and IL‐18 show promise as early AKI diagnostic tests in children treated with ifosfamide and may have a potential role in drug toxicity monitoring.